Tracing the contribution of childhood studies: Maintaining momentum while navigating tensions. (February 2020) - Canosa, Antonia; Graham, Anne
Over recent decades, the evolving field of childhood studies has contributed significantly to the theorisation of childhood and to research seeking to understand children's lives and experiences in different contexts. This article traces some of the key theoretical developments within childhood studies by means of a scoping study of peer-reviewed, scholarly journals and books published between 2010 and 2018. The aim of the review was to explore the theoretical and empirical contributions of childhood studies beyond its early foundational tenets. A number of emerging tensions were identified and these are explored in this article.